HUBUNGAN ANTARA PRAKTIK ANTENATAL CARE PADA KEHAMILAN REMAJA DENGAN ANEMIA DI BOGOR - Koerniawati, Ratu Diah; Briawan, Dodik; Rimbawan, Rimbawan (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2016)
The objective of this research was to study antenatal care (ANC) practices and its association to anaemia on adolescent pregnancies. A cross-sectional design was applied in Bogor City between January to March 2016. A number of 72 pregnant adolescents (aged 10-19 years) participated in the study. Hemoglobin was collected through venous blood and analyzed with cyanmethemoglobin method. Data analysis using Chi-square test. The result showed that 30.6% of pregnant adolescent came lately for their first visit of antenatal care (missed first trimester). Overall, the prevalence of anaemia (Hb <11 g/dl) was found to be 45.8%. There was no significant association between anaemia with consumption of iron supplementation, energy intake, iron intake, and vitamin C intake (p>0.05). However, there was a significant association between protein intake and anaemia (p<0.05). Antenatal care pratices on adolescencts pregnancy was low. Many of them had anaemia in their pregnancy. Protein intake should be increased to reduce the incidence of anemia in adolescents pregnancy.Keywords: anaemia, antenatal care, pregnant adolescent